Operational Performance of Privately Owned Ship - Muhammad Wildan Rizkyansyah; Sri Untung; Imam Sonny (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
The purpose of this study is to determine and identify the effect of warehouse infrastructure and spare parts procurement on ship operational performance with the effectiveness of ship maintenance as an intervening variable on ships owned by PT Mitrabahtera Segara Sejati Tbk in 2020. Methods of data analysis use linear regression analysis, simple correlation, partial or simultaneous and path analysis. Based on the analysis and discussion, it shows that there is a significant positive direct effect of warehouse infrastructure on the effectiveness of ship maintenance, there is a significant positive direct effect of spare parts procurement on the effectiveness of ship maintenance, there is a significant positive direct effect warehouse infrastructure on ship operational performance, direct positive which is significant the procurement of spare parts on the operational performance of the ship, there is a significant positive direct effect of the effectiveness of ship maintenance on the operational performance of the ship, there is an intervening effect between warehouse infrastructure on the operational performance of the ship through the effectiveness of ship maintenance and there is an intervening effect between the procurement of spare parts on vessel operational performance through effective ship maintenance on vessels owned by PT Mitrabahtera Segara Sejati Tbk.